Impact of social position and agency on ready-made garment workers' food security in urban Bangladesh - Haque, Sadika; Khan, Md Sahed; Mawa, Bentul; Sarkar, Md Abdur Rouf; Misu, Nushrat Jahan; Farquhar, Samantha; Salman, Md; Akter, Mohima; Afrin, Khandaker Sadia; Sarowar, Samiha; Sarker, Mou Rani; Hoque, Md Nazmul; et al. (Springer Nature, 2025)
Female ready-made garment (RMG) workers are major contributors to Bangladesh’s economy, yet they struggle to afford basic nutritious food owing to their minimal earnings as urban migrants. Their situation toward food is aggravated by their limited agency and lower social status as women and RMG workers, along with highly gendered food accessibility and utilization within the households. This article examines how the limited agency and social status of these RMG workers impact their food security outcomes through an ethnographic lens. Individual in-depth interviews and focus group discussions were conducted with female RMG workers, their husbands, community members, and other relevant stakeholders to gather evidence. Our findings show that most women RMG workers struggle to achieve food security, especially in terms of affordability and utilization. Many of these workers are constantly facing psychological deprivation toward food items that they would prefer, generating mental insecurity for food. The novel of ‘Food Desire’ dimension is integrated in this work. The situation of these RMG workers is worsened by socio-cultural norms that restrict their social food access. To address these compounded problems, this study recommends stabilizing food prices, implementing holistic salary revisions considering inflation rates, and introducing gender-responsive social safety net programmes for RMG worker households.